Effects of Rinse using Black Tea Solution (Blessed Tea) in Reducing Plaque Accumulation in Dental of Elementary School Children - Pujirahayu, Rahminingrum (Jurnal Keperawatan Terapan, 2020)
The number of dental and oral problems in Indonesia is still quite high, especially dental caries. The purpose of this study was to determine the effect of rinsing using black tea solution or Bless tea in reducing plaque accumulation in dental elementary school children. This type of research is quasi-experimental with pre-test and post-test group design. The study was conducted at SD Negeri 51 Poasia Kendari City. Respondents were selected based on the total sampling method in the students of SD Negeri 51 Poasia Kendari, aged 7-8 years and obtained as many as 40 respondents. The research variables are black tea solution (bless tea) and dental plaque. The research procedure begins with the initial examination of plaque before and after the intervention using a disclosing solution. Measurements use the Patient Hygiene Performance Index or PHP-Index instrument. The average before rinsing using black tea solution was 3.10 and the average after rinsing using black tea solution was 1.81. There was a decrease with the difference before and after 1.09. The analysis showed that there was a significant difference between plaque accumulation data before and plaque accumulation data after rinsing the black tea solution, p is 0,000. Decreased dental plaque accumulation in the treatment group with black tea solution, 1.10 and the mean reduction in dental plaque accumulation in the chlorhexidine control group was 0.2%. The results of the analysis showed a significant difference between the reduction in dental plaque accumulation in the intervention group and the control group, p is 0.03. The reduction in plaque accumulation in the intervention group rinsed with a black tea solution was smaller than the control group rinsed with 0.2% chlorhexidine. The conclusion of the study is that there is an effect of rinsing the black tea solution in Reducing the Accumulation of Dental Plaque in Primary School Children aged 7-8 years.